Mechanically Robust, Electrically Conductive and Stimuli‐Responsive Binary Network Hydrogels Enabled by Superelastic Graphene Aerogels. (14th March 2014) - Qiu, Ling; Liu, Diyan; Wang, Yufei; Cheng, Chi; Zhou, Kun; Ding, Jie; Truong, Van‐Tan; Li, Dan
<x xml:space="preserve">Abstract</x> The architecture of the nanofiller phase in polymer nanocomposites matters! Polymer hydrogels that can combine stimuli‐responsiveness with excellent electrically conductivity and mechanical strength can be fabricated by incorporation of the polymer into an ultralight and superelastic graphene aerogel to form a binary network. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>